Blood biochemical and physical parameters of crossbred barrows reared with different floor space allowances (Indian Journal of Animal Production and Management, 2024)
To compare the effect of different floor space allowances on physiological status of pigs, 36 crossbred  (Landrace x Desi) barrows were reared with 3 different floor space allowances {n = 4(group size) x  3(replications) = 12 each}. Group TIS (control) had floor space allowance (0.9, 1.35 and 1.8 m2/pig during  weaner, grower and finisher stage) as per Indian Standards (IS: 3916-1966), while T2/3 and T1/2 treatment  groups had 33% and 50% reduced floor space allocation with fixed small (n=4) group size throughout the  experiment. Skin lesion score, blood parameters and back fat thickness (BFT) of pigs were estimated.  Mean skin lesion score of head and ears (weaner, P
Keywords: Back fat thickness; Crossbred barrow; Floor space; Lesions; Welfare